Dialectical Thinking: A Proposed Foundation for a Post-modern Psychology - Veraksa, Nikolay; Basseches, Michael; Brandão, Angela (Frontiers in Psychology, 2022)
For the authors, the way from a modern to a post-modern psychology requires dialectical thinking. Dialectical thinking recognizes the importance of contradiction, change, and synthesis; it also includes recognition of the value as well as limits of modern epistemological approaches. The article describes foundations for both ongoing efforts to understand and research the ontogeny of dialectical thinking and for appreciating the scope of dialectical thinking and its relevance for establishing a bridge from modern to post-modern psychology.